In-Vitro Evaluation of Two Types of Neonatal Oxygenators in Handling Gaseous Microemboli and Maintaining Optimal Hemodynamic Stability During Cardiopulmonary Bypass - Marupudi,Neelima (2016)
Abstract Objective: Usually only FDA-approved oxygenators are subject of studies by the international scientific community. The objective of this study is to evaluate two types of neonatal membrane oxygenators in terms of transmembrane pressure gradient, hemodynamic energy transmission and gaseous microemboli capture in simulated cardiopulmonary bypass systems. Methods: We investigated the Braile Infant 1500 (Braile Biomédica, São José do Rio Preto, Brazil), an oxygenator commonly used in Brazilian operating rooms, and compared it to the Dideco Kids D100 (Sorin Group, Arvada, CO, USA), that is an FDA-approved and widely used model in the USA. Cardiopulmonary bypass circuits were primed with lactated Ringer's solution and packed red blood cells (Hematocrit 40%). Trials were conducted at flow rates of 500 ml/min and 700 ml/min at 35ºC and 25ºC. Real-time pressure and flow data were recorded using a custom-based data acquisition system. For gaseous microemboli testing, 5cc of air were manually injected into the venous line. Gaseous microemboli were recorded using the Emboli Detection and Classification Quantifier. Results: Braile Infant 1500 had a lower pressure drop (P<0.01) and a higher total hemodynamic energy delivered to the pseudopatient (P<0.01). However, there was a higher raw number of gaseous microemboli seen prior to oxygenator at lower temperatures with the Braile oxygenator compared to the Kids D100 (P<0.01). Conclusion: Braile Infant 1500 oxygenator had a better hemodynamic performance compared to the Dideco Kids D100 oxygenator. Braile had more gaseous microemboli detected at the pre-oxygenator site under hypothermia, but delivered a smaller percentage of air emboli to the pseudopatient than the Dideco oxygenator.